Long-Term Trends in Extreme Rainfall and Impact on Rice Productivity and Vegetation Condition in West Java (Agromet, 2026)
Climate change has intensified the frequency and magnitude of extreme rainfall events, posing significant challenges to agricultural productivity in tropical regions such as Indonesia. Understanding the spatial-temporal patterns of extreme indices is crucial for mitigating the risk of crop failure and maintaining regional food security. This study examines the trends and patterns of extreme climate indices and their impact on rice productivity and vegetation conditions in West Java based on spatio-temporal analysis. We utilized several extreme climate indices including RX1day, RX5day, R95p, R99p, CWD, and PRCPTOT for 1991–2023 using daily rainfall data from 242 stations in West Java. We analyzed the relationships between climate variability, annual rice productivity and vegetation density using Normalized Different Vegetation Index (NDVI). Our results reveal increasing trends in the intensity and frequency of RX5day, PRCPTOT, and CWD, particularly in central and northern West Java. But, we found a weak correlation between extreme climate indices and rice productivity, with statistically significant (p < 0.05) only in certain areas. The long-term rice productivity showed a decline after 2020, coinciding with the intensification of extreme rainfall. In addition, vegetation density shows significant negative responses to extreme climate indices in several regions. This study provides an integrative framework linking extreme climate indices, agricultural productivity, and vegetation dynamics to support evidence-based climate change adaptation strategies.